Van Wyk-Grumbach syndrome a great masquerader of primary hypothyroidism - Beatrice Anne; Vivek Kumar; Mounica Tavva (Journal of Clinical and Scientific Research)
Children with primary hypothyroidism typically present with delayed growth and development, precocious puberty but on rare occasions can present with pituitary macroadenoma. This is called Van Wyk-Grumbach syndrome (VWGS). A young girl aged 8 years presented to our clinic with premature menarche and isosexual precocity. She had delayed bone age and multicystic ovaries. High circulating levels of thyroid-stimulating hormone (TSH) with prepubertal luteinising hormone confirmed the diagnosis of VWGS. Sexual precocity in VWGS may be directly related to the severity of the TSH elevation. High circulating levels of TSH acting directly on follicle-stimulating hormone receptors are the actual mediators of precocity. Most cases of hypothyroidism result from autoimmune thyroid destruction, and usually all manifestations regress after the initiation of adequate thyroid hormone replacement. The probable mechanism of this unusual presentation is structural homology between the different glycoprotein hormones acting through G-protein-coupled receptors.